2019
DOI: 10.1016/j.ebiom.2019.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Tumor grading of soft tissue sarcomas using MRI-based radiomics

Abstract: a b s t r a c tBackground: Treatment decisions for multimodal therapy in soft tissue sarcoma (STS) patients greatly depend on the differentiation between low-grade and high-grade tumors. We developed MRI-based radiomics grading models for the differentiation between low-grade (G1) and high-grade (G2/G3) STS. Methods: The study was registered at ClinicalTrials.gov (number NCT03798795). Contrast-enhanced T1-weighted fat saturated (T1FSGd), fat-saturated T2-weighted (T2FS) MRI sequences, and tumor grading followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
81
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(100 citation statements)
references
References 36 publications
8
81
1
1
Order By: Relevance
“…Our results also deepened that intra-tumoral heterogeneous SIs on T2-WI is predictive of MFS in a quantitative manner and other studies have also correlated this parameter with overall and/or metastatic-relapse free survivals in STS patients with relatively close and similar performances to ours 6,7,20 . Indeed, Peeken et al used an equivalent of IHTstd and applied ComBat to correct for multicenter effect.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our results also deepened that intra-tumoral heterogeneous SIs on T2-WI is predictive of MFS in a quantitative manner and other studies have also correlated this parameter with overall and/or metastatic-relapse free survivals in STS patients with relatively close and similar performances to ours 6,7,20 . Indeed, Peeken et al used an equivalent of IHTstd and applied ComBat to correct for multicenter effect.…”
Section: Discussionsupporting
confidence: 82%
“…In this case, lowering these performances with a particular IHT would mean that this IHT caused noise and inappropriate deviation in the data. However, as already stated, prior studies converged towards same results regarding the relationship between MRI-based radiomics features, heterogeneity on T2-WI and outcomes of sarcoma patients 6,7,20,35 . Alternative study designs could have been proposed in the absence of such relationship, (i) either by using a phantom made of compartments with various degrees of heterogeneity, (ii) or by using MRIs of healthy volunteers covering organs with different textures and investigating which IHT enables the best radiomics-based classification of these organs (by analogy with the study by Orlhac et al) 19 .…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Spraker et al [20] found that radiomics features alone or combined with age and grade were respectively independent predictors of over survival, and the latter achieved best performance. Peeken et al [37] demonstrated that the radiomics model based on T1FSGd MRI sequences showed signi cant patient strati cation performance for overall survival, and improved prognostic performance was found with the combination of a T2FS radiomics model with the AJCC system. Conversely, we evaluated survival prediction by incorporating a nomogram-predicted grade model that included clinical stage and MRI features, and it showed superior patient risk strati cation performance.…”
Section: Discussionmentioning
confidence: 99%